The bridge of San Luis Rey - Wilder, Thornton, 1897-1975; Drevenstedt, Amy, 1886- (Salt Lake City, UT : Project Gutenberg, 2023)
"The Bridge of San Luis Rey" by Thornton Wilder is a novel published in 1927. When an ancient rope bridge in Peru collapses in 1714, five travelers plunge to their deaths. A Franciscan friar who witnesses the tragedy becomes obsessed with understanding why these particular people died at that moment. He spends six years investigating their lives, searching for evidence of divine purpose in what appears to be random catastrophe. The novel weaves together the stories of the victims, revealing the hidden connections and intimate struggles that led them to the bridge. (This is an automatically generated summary.)
Perhaps an accident -- The Marquesa de Montemayor -- Esteban -- Uncle Pio -- Perhaps an intention.
Wikipedia page on this work: https://en.wikipedia.org/wiki/The_Bridge_of_San_Luis_Rey
Release date is 2023-01-11
Laura Natal Rodrigues (Images generously made available by Hathi Trust Digital Library.)
Keywords: Historical fiction; Peru -- Fiction; Accident victims -- Fiction; Bridges -- Accidents -- Peru -- Fiction